Species Composition and Hydrolase Enzyme (EC.3) Activity of Fungi Isolated from Thasala Mangroves, Nakhon Si Thammarat Province, Southern Thailand - Ungcharoenwiwat, Pakpimol; Sakayaroj, Jariya (Trends in Sciences, 2022)
In the present study, we aimed to investigate diversity of manglicolous and endobiotic fungi associated with mangrove plants from Thasala mangroves, Nakhon Si Thammarat province, southern Thailand. Extracellular hydrolase enzymes (EC.3) including amylase, cellulase, lipase, protease, and pectinase from isolated fungi were evaluated. A total of 31 obligate marine fungal species was recorded from various Thasala mangroves sites. These included 24 ascomycetes (77.4 %), 1 mucoromycete (3.2 %), 3 basidiomycetes (9.7 %), 4 asexual morphs (12.9 %), and tentatively identified fungi (9.7 %). The average percentage occurrence of the fungi recorded from each site ranged from 0.4 to 16%. At all sites, the common filamentous marine fungi were Cumulospora sp., Halorosellinia oceanica, Kallichroma tethys, Leptosphaeria sp., Rimora mangrovei, Lulworthia sp., Phoma sp., Halenospora varia, Halocyphina villosa, Nia vibrissa, and Sclerococcum haliotrephum. Also, the most frequent marine fungi include Eutypella naqsii, Sammeyersia grandispora, Marinosphaera mangrovei, Nemania maritima, and Verruculina enalia. Seven mangrove plants were selected for endophytic fungal isolation including Acanthus ebracteatus, Acrostichum aureum, Avicennia alba, Bruguiera cylindrica, Rhizophora apiculata, R. mucronata, and Sonneratia alba. The isolation rate (IR) and colonization rate (CR) of fungal endobiota varied for all plant studied. The isolation rate ranged from 24 - 53.3 %, while colonization rate varied from 29.3 - 61.3 %. The fungal isolates were screened for the production of hydrolase enzymes (EC.3), of which 37.2 % exhibited enzyme activities. The 16 out of 28 obligate marine fungi (57.1 %) and 13 out of 50 fungal endophytes (26 %) had enzyme production efficiency toward specific substrates or an enzymatic index (EI) higher than 1.4. None of the fungal isolates depicted lipase activity. Additionally, the environmental stressors (temperature, pH, salinity) affecting enzyme production were evaluated in order to discover potential candidates for industrial application. HIGHLIGHTS Diversity of obligate marine fungal species was estimated from Thasala mangroves The obligate marine fungi and fungal endophytes had hydrolase enzyme (EC.3) production efficiency toward specific substrates or an enzymatic index (EI) higher than 1.4 The temperature, pH, and salinity affecting enzyme production were evaluated in order to discover potential candidates for industrial application GRAPHICAL ABSTRACT